STEAM-Based Augmented Reality Media: Enhancing Gender-Responsive Pedagogy in Indonesian Early Childhood Education - Ratu Yustika Rini; Inten Risna; Sigit Auliana (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study aims to develop and evaluate STEAM-based Augmented Reality (AR) learning media to enhance teachers’ competence in implementing gender-responsive pedagogy in early childhood education. Employing the ADDIE research and development model, the study involved 31 early childhood teachers in Walantaka District. The feasibility of the developed media was assessed by content experts, media experts, and practitioners, while its effectiveness was evaluated through pre- and post-test measures. The findings indicate that the AR-based learning media demonstrated very high feasibility, with an average validation score of 88% (ranging from 86% to 90%). The effectiveness analysis yielded an N-Gain score of 0.67, indicating a substantial improvement in teachers’ competence in applying gender-responsive pedagogical practices. The developed media presents professional roles in a balanced and non-stereotypical manner and integrates STEAM principles to foster critical thinking, creativity, and problem-solving skills. The study concludes that STEAM-based AR learning media are effective in supporting the implementation of gender-responsive pedagogy in early childhood education. By embedding gender equality principles into immersive digital learning experiences, this research contributes to inclusive instructional design and provides educators with practical tools. Future studies are recommended to involve larger and more diverse samples, examine long-term impacts on classroom practices, and explore the integration of AR-based gender-responsive media across different educational contexts and learning domains.